Fintech: Is this time different? A framework for assessing risks and opportunities for central banks - Meyer Aaron; Francisco Rivadeneyra; Samantha Sohal (Bank of Canada, 2017)
We investigate the risks and opportunities to the mandates of central banks arising from fintech developments. Fintech may affect the different areas of responsibility of central banks - mainly monetary policy and financial stability - by changing money demand and by changing the industrial organization of the financial system. We present a competitive strategy framework to help evaluate the likelihood of these changes.
Keywords: G1; G2; L1; E42; 330; Central bank research; Digital currencies; Financial institutions; Payment clearing and settlement systems